Reactive Structures of Ammonia MILD Combustion in Diffusion Ignition Processes - Sorrentino, G.; Sabia, P.; Ariemma, G. B.; Ragucci, R.; de Joannon, M. (Frontiers in Energy Research, 2021)
Reactive structures have been analyzed, when ammonia is used as a fuel, in a steady 1D counterflow diffusion flame layer, mimicking diffusion ignition processes. The characterization has been carried out in a wide range of feeding parameters under Moderate or Intense Low-oxygen Dilution (MILD) combustion conditions. Both the Hot-Fuel-Diluted-Fuel (HFDF) and Hot-Oxidant-Diluted-Fuel (HODF) configurations were studied to analyze the main effects of the inlet feeding conditions on the oxidative structures. The reaction zone has been analyzed in terms of temperature and heat release profiles in the mixture fraction space for various ranges of inlet parameters, using a standard code and a validated chemical kinetic scheme. Several features of the reaction zone have been recognized as reported also in previous works for hydrocarbon flames. They were used as discriminative for the achievement of various combustion regimes. In particular, the flame thickening process and the absence of correlation between the maximum heat release and the stoichiometric mixture fraction were analyzed to build maps of behaviors. The latter were reported on an inlet preheating level-temperature increase plane for fixed values of the bulk strain rate and system pressures. Another relevant feature previously reported with hydrocarbons in the literature, in Hot Diluted Diffusion Ignition (HDDI) processes under MILD conditions, was the pyrolysis depression. The latter characteristic has been not observed when ammonia is used as a fuel, for the operative conditions here investigated. Indeed, the heat release profiles do not show the presence of negative heat release regions. The results obtained for the HFDF configuration are strongly dependent on the system pressure level. Finally, the HODF condition has been also analyzed for ammonia at the atmospheric pressure. Boundaries of the combustion regimes and reactive structure features showed several differences between HFDF and HODF cases with respect to the inlet parameters.